THE ROLE OF BUSINESS MODEL CANVAS (BMC) IN DIGITAL ENTREPRENEURSHIP ON STUDENTS' INTEREST IN INDONESIA - rizan, mohamad; sumastuti, efriyani; prabowo, heri; kresnamurti, agung; Chalida Hanoum, Farah (Fakultas Ekonomi, Universitas Negeri Jakarta, 2024)
Unemployment of the productive age population is a big challenge for Indonesia entering the era of free markets and global competition. Creating young entrepreneurs is a solution that can be done to strengthen economic growth. Indonesia produces 700 thousand graduates annually, but many Indonesian students show limited interest in entrepreneurship. A lack of understanding of entrepreneurship makes students more likely to find jobs than create jobs. This research aims to provide an understanding to students regarding the importance of entrepreneurship and stimulate the growth of an entrepreneurial mindset among them. This is achieved by introducing and understanding in depth the Business Model Canvas (BMC), so that students can start and run businesses, so as to be able to transform them into job creators. The research method used is a causal / explanatory survey, using primary data collected through participatory observation, interviews, and questionnaires distributed to selected public and private universities in Indonesia using convenience / accidental sampling techniques. The questionnaire was distributed to a total of 200 respondents, in accordance with the minimum sample size requirements for the Structural Equation Modeling (SEM) analysis technique, using LISREL software version 8.8. The findings of this study show that customer segments, value proportions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structures are able to increase entrepreneurial interest. Business Model Canvas (BMC) effectively increases students' understanding of entrepreneurship. BMC's simplicity in mapping and presenting business models makes it an effective tool to deepen business understanding. However, BMC is not an instant tool that can necessarily improve students' entrepreneurial mindset. Understanding BMC is the same as other sciences that cannot be taught in a short time and requires a process to learn it. The timeframe available in the study was very short and did not meet the requirements to cultivate a mindset that was truly expected to prepare students to engage fully as entrepreneurs.